Risk, regulation, and investor protection: The case of investment management - Franks, J; Mayer, C (Oxford University Press, 1989)
Investigates whether capital requirements are an appropriate form of investor protection and whether the amounts that the Investment Management Regulatory Organization has required of its members are correct. Describes the investment management business in the United Kingdom, the function that investment managers perform, and the risks to which those functions give rise. Discusses recent examples of investment managers in the United Kingdom who have failed their clients due to fraud, negligence, or pure financial risk, and draws lessons from these cases for the design of investor protection. Surveys the relevant academic literature on corporate capital structures, capital requirements for banks, and regulating the professions. Identifies the market failures that create a need for investor protection and addresses the question of how that protection should be provided, considering the case for capital requirements, as well as the merits and deficiencies of alternative methods. Describes and evaluates the current Investment Management Regulatory Organization rules on capital requirements. Examines the regulation of investment management firms in the United States. Franks is National Westminster Bank Professor of Finance at the London Business School. Mayer is Professor of Corporate Finance at the City University Business School. Index.